In vitro shear bond strength test and failure mechanism of zinc phosphate dental cement - P. Odthon (2018)
© 2015PublishedbyElsevierLtd. The cohesive shear bond strength (SBS) of hardened zinc phosphate cement (CeCe) was comparatively measured with those of the adhesive SBS of the human dentin-cement (DCe), artificial acrylic crown-cement (CrCe), dentin-cement-crown (DCeCr). Results from experiments found that the SBS of CeCe specimen is much higher than those of the adhesive SBS. The average maximum SBS of CeCe, DCe, DCeCr and CrCe specimens of approximately 6.91, 1.02, 0.67 and 0.25 MPa, are respectively obtained. Fractographs taken by scanning electron microscope and close-up camera images of the fracture surfaces were analyzed for their failure mechanisms. The crack initiation and propagation of DCe and CrCe bonding types occur along the bonding interface. In the DCeCr bonding type, the crack initiates at crown-cement interface, propagates downward and changes in to the dentin-cement interface until failure. The average fracture area ratio of the CrCe interface to DCe interface of about 85:15 are observed for the DCeCr de-bonded specimens. Results from force and stress analysis using the two point bonding model indicate that the shear stress is more evident for the bond fracture.